A systematic review of teacher talk and its effects on English language learning outcomes - Linlin, Zou; Jeyaraj, Joanna Joseph; Ismail, Lilliati (Sciedu Press, 2024)
Teacher talk in language classes plays a crucial role in students' understanding and development within the discipline. This study systematically reviews previous research on teacher talk and its impact on students' learning outcomes in English language classrooms. 25 articles, published between 2018 and 2023, focusing on teacher talk and students' learning outcomes, were selected and reviewed. The aim was to discern the publication trends regarding teacher talk and its influence on students' learning achievement. The results indicated that research on teacher talk is predominantly welcomed in English-speaking countries. Additionally, the study participants in the 25 selected articles are primarily teachers and students from kindergarten, primary, and secondary schools. The research outcomes vary across the selected articles, with the majority highlighting the positive effects of teacher talk on students' learning outcomes, such as enhancement of English language skills and development of social and emotional skills, although some articles also report null or negative effects. Further research is recommended to investigate the detailed characteristics of teacher talk and their impact on student learning outcomes in secondary school and university classrooms.